2010
DOI: 10.1007/s10815-010-9399-2
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolated oocytes: fertilization and embryonic arrest following intra-cytoplasmic sperm injection in a patient exhibiting persistent oocyte macro vacuolization—Case report

Abstract: It is likely that persistent Oocyte Macro Vacuolization is the cause of infertility in this patient. It probably has a biological basis and possibly a genetic cause, resulting in either uncontrollable endocytosis or poor exocytosis and consequent vacuolar formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
(27 reference statements)
3
15
0
Order By: Relevance
“…In the present study, the high viscosity of the cytoplasm and vacuoles had a negative influence on fertilization rates; this finding is consistent with several previous studies . However, our finding also demonstrated a positive impact of the presence of dark ZP on fertilization rate, which indicates that some features of morphological changes of oocyte can have a positive impact on fertilization rate.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the high viscosity of the cytoplasm and vacuoles had a negative influence on fertilization rates; this finding is consistent with several previous studies . However, our finding also demonstrated a positive impact of the presence of dark ZP on fertilization rate, which indicates that some features of morphological changes of oocyte can have a positive impact on fertilization rate.…”
Section: Discussionsupporting
confidence: 93%
“…The multiple anomalies and the high number of degenerated oocytes indicates that these oocytes endured serious intrinsic adverse effects during oogenesis and maturation. The present report confirms previous findings (Akarsu et al, 2009;Wallbutton and Kasraie, 2010) and clearly shows that oocyte anomalies can be a recurrent phenomenon in the same patient.…”
Section: Discussionsupporting
confidence: 93%
“…Determining the effect of a single oocyte dysmorphism is quite difficult because many oocytes show more than one morphological abnormality (De Sutter et al, 1996). It has also been reported that serious oocyte dysmorphisms, such as clusters and vacuoles in the cytoplasm, can be a recurrent phenomenon in consecutive IVF treatments for the same patient (Akarsu et al, 2009;Wallbutton and Kasraie, 2010). In these cases, it is often difficult to counsel patients as to how to proceed.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to various toxicants caused ooplasmic vacuolization in fish (Akbulut, Dinc, Genc, Zengin, & Deniz, 2018;Saravanan, Uma, & Jothi, 2016). In clinical in vitro fertilization, oocyte vacuolization is a common observation and suggested as due to uncontrollable endocytosis or poor exocytosis (Balaban et al, 2008;Wallbutton & Kasraie, 2010). The ovarian disruption could also be due to hormonal imbalance in response to salinity stress.…”
Section: Discussionmentioning
confidence: 99%